2014
DOI: 10.1016/j.psychres.2014.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Disinhibited reactive attachment disorder symptoms impair social judgements from faces

Abstract: SummaryTypically developing adults and children can rapidly reach consensus regarding the trustworthiness of unfamiliar faces. Maltreated children can have problems with trusting others, yet those with the disinhibited form of Reactive Attachment Disorder (dRAD) can be indiscriminately friendly. Whether children with dRAD symptoms appraise and conform to typical judgements about trustworthiness of faces is still unknown. We recorded eye movements of 10 maltreated dRAD children and 10 age and gender matched typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…On the other hand, there is an emerging body of research on attachment disorders in school age children and adolescents. This research has demonstrated that signs of RAD and DSED are demonstrable in school-aged children and adolescents with histories of institutional rearing and maltreatment who are adopted 61,[68][69][70][71] or placed in foster care [72][73][74] but also studies identifying these disorders in impoverished populations of children in whom maltreatment is not specifically identified. 75,76 Two studies have demonstrated discriminate validity of RAD compared to ASD 77, and ADHD.…”
Section: Emerging Data In Older Childrenmentioning
confidence: 97%
“…On the other hand, there is an emerging body of research on attachment disorders in school age children and adolescents. This research has demonstrated that signs of RAD and DSED are demonstrable in school-aged children and adolescents with histories of institutional rearing and maltreatment who are adopted 61,[68][69][70][71] or placed in foster care [72][73][74] but also studies identifying these disorders in impoverished populations of children in whom maltreatment is not specifically identified. 75,76 Two studies have demonstrated discriminate validity of RAD compared to ASD 77, and ADHD.…”
Section: Emerging Data In Older Childrenmentioning
confidence: 97%
“…Trust is essential for the development of secure, healthy relationships. A sense of trust in family and peers is primarily based on environmental factors (Miellet, Valdara, Gillberg, Raju, & Minnis, 2014). Having the ability to trust can decrease the likelihood of problems such as isolation, bullying, and depression (Sakai, 2010).…”
Section: Consequencesmentioning
confidence: 99%
“…Children with attachment disorders have problems with trust. Those with the RAD type have difficulty truly trusting anyone, even a kind, consistent caregiver, whereas those with DSED trust indiscriminately, and this poor judgement places them at increased risk for physical, sexual, and emotional harm (Miellet et al, 2014). Children with attachment disorders also lack empathy (Zeanah et al, 2016).…”
Section: Consequencesmentioning
confidence: 99%
“…Children with IF were found to present with a series of neurodevelopmental problems such as attention deficit hyperactivity disorder and post-traumatic stress disorder in a study of 34 adoptees in comparison with 32 nonadopted children raised by birth parents (Kočovská et al, 2012). In another study by Miellet, Caldara, Raju, Gillberg, and Minnis (2014), children with IF failed to show consensus on trustworthiness and attraction in presenting faces, whereas children without IF were able to reach an agreement demonstrated by previously tested adults. Concerns were thus held on trustworthiness and attractiveness judgments of children with IF.…”
Section: Ifmentioning
confidence: 75%